2006
DOI: 10.1002/ijc.21774
|View full text |Cite
|
Sign up to set email alerts
|

New immunochemical fecal occult blood test with two‐consecutive stool sample testing is a cost‐effective approach for colon cancer screening: Results of a prospective multicenter study in Chinese patients

Abstract: The purpose of the study is to evaluate a new immunochemical fecal occult blood test method (Hemosure IFOBT), and compare it to the Guaiac-based chemical method (CFOBT) for colorectal cancer detection. A hypothetical sequential method (SFOBT), in which IFOBT was used only as a confirmatory test for CFOBT, was also evaluated. A total of 324 patients were recruited from 5 major hospitals in Beijing, China. For each patient, 3 consecutive stool samples were collected for simultaneous CFOBT and IFOBT tests, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 14 publications
1
29
0
5
Order By: Relevance
“…The studies that evaluated the standard guaiac-based FOBT that did not correct for verification bias are listed in Table 1. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] In the last study, the data was presented in two separate publications. These 19 studies included 713 subjects with colorectal cancer and 4181 controls.…”
Section: Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies that evaluated the standard guaiac-based FOBT that did not correct for verification bias are listed in Table 1. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] In the last study, the data was presented in two separate publications. These 19 studies included 713 subjects with colorectal cancer and 4181 controls.…”
Section: Included Studiesmentioning
confidence: 99%
“…Both control-and cancersubjects underwent a confirmatory test, usually a colonoscopy though some of the older studies also utilized barium enema and sigmoidoscopy, particularly if FOBT negative. Most studies included subjects who submitted 3 stool specimens [31][32][33][34]36,37,39,41,44,[46][47][48][49][50] while some studies included subjects who only submitted one specimen 35,42,43 or the number was not specified. 38,40,45 Almost all of the studies reported that the specimens were collected at home while one study did not specify the location.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Respecto a los estudios que han evaluado el coste-efectividad de ambos tests, dos concluyeron que el inmunológico era, como mínimo, igual de efectivo que el guayaco pero más barato 27,28 . En otro estudio, la utilización del test inmunológico durante 20 años en un cribado bienal aumentaba 59 euros más que el guayaco por individuo y la media de la esperanza de vida en 0,0198 años, lo que corresponde a un incremento de la ratio coste-efectividad de 2.980 euros por año de vida salvada 29 .…”
Section: Discussionunclassified
“…Fecal occult blood test, especially IFOBT, is a wellaccepted effective screening method for colorectal cancers (12)(13)(14). The main detection target in IFOBT is fecal hemoglobin.…”
Section: Discussionmentioning
confidence: 99%